What kind of history teaching may promote intercultural competence in culturally-diverse societies? Teachers’ reflections from a case of conflict - Hajisoteriou, Christina; Solomou, Emilios A.; Antoniou, Mary (Frontiers in Education, 2023)
In our globalised world, the goal of cultivating a rigid national identity through school history should be replaced by the goals of developing global citizenship and safeguarding democracy.School history should thus balance the feeling of belonging to the state with the feeling of being a global citizen by building students' intercultural competence through historical thought, conscience, and empathy. To this end, the main purpose of this research is to examine teachers' perceptions of the best teaching strategies and practices to cultivate students' intercultural competence through history education. The study is implemented in Cyprus, as it provides for a context of conflict, in which history education is called to play a catalytic role in building reconciliation. Interviews were carried out with 18 high-school history teachers. Based on their perspectives, three thematic categories emerged from the data analysis; namely: (a) history teaching through an interdisciplinary approach, (b) history teaching through historical sources, and (c) history teaching through collaborative learning. The study bears wider implications for history curricula, teaching methodologies, and teachers' training.